The naming and framing of nuclear energy by the Belgian government and the nuclear lobby: a critical discourse analysis - Van Impe, Michelle (2017)
Nuclear energy is a controversial topic in Belgium and the government strives for a nuclear exit by 2025. However, there are few notable policy efforts which prepare us for such a future. The framing of nuclear energy is crucial in the ongoing debate about its usage. In this paper, we analyse the discourse of the nuclear lobby and government through a green criminological lens. We compare the discourse with academic literature about nuclear energy and identify ideological strategies via the analytical framework of Larrain (1983)